One‐Pot Synthesis of Pyrazoles through a Four‐Step Cascade Sequence. Issue 18 (28th February 2013) - Hao, Lu; Hong, Jun‐Jie; Zhu, Jun; Zhan, Zhuang‐Ping
Abstract A one‐pot synthesis of 3, 4, 5‐ and 1, 3, 5‐pyrazoles from tertiary propargylic alcohols and para‐tolylsulfonohydrazide has been accomplished. The pyrazoles are formed through a four‐step cascade sequence, including FeCl3‐catalyzed propargylic substitution, aza‐Meyer–Schuster rearrangement, base‐mediated 6π electrocyclization, and thermal [1, 5] sigmatropic shift. In this reaction, the 3, 4, 5‐ and 1, 3, 5‐pyrazoles are produced selectively according to different substituents in the starting alcohols.